2023
DOI: 10.5005/jp-journals-10018-1379
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Comparison of Different Prognostic Scores in Wilson\'s Disease

Abstract: A bstract Aim Wilson's disease (WD) is a rare autosomal recessive disease, that can involve any organ of the body, the main ones being the liver and the brain. These patients can have varied presentations, ranging from having no symptoms to having neurological manifestations to features of chronic liver disease (CLD). Those patients that end up having CLD are prognosticated via the Child–Turcotte–Pugh (CTP) score and the Model for End-stage Liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Additionally, there are several other scores: the revised Nazer King's prognostic score in WD (the New Wilson Index) published by Anil Dhawan et al in 2005 to assist management decisions in patients with acute liver injury, [121] the Unified Wilson's Disease Rating Scale proposed by Anna Czlonkowska et al in 2007 [122] (later evaluated [123] ), and also a Global Assessment Scale from Aggarwal et al [124] While these can be used to score the clinical features in patients with WD, other comparisons of various rating scales in WD have also been published. [125] As with other clinically applicable scores and indices, it is mandatory to review such calculations periodically, as experience with other prognostic instruments has shown that their reliability may need to be scrutinized [126] from time to time.…”
Section: Cu 1+mentioning
confidence: 99%
“…Additionally, there are several other scores: the revised Nazer King's prognostic score in WD (the New Wilson Index) published by Anil Dhawan et al in 2005 to assist management decisions in patients with acute liver injury, [121] the Unified Wilson's Disease Rating Scale proposed by Anna Czlonkowska et al in 2007 [122] (later evaluated [123] ), and also a Global Assessment Scale from Aggarwal et al [124] While these can be used to score the clinical features in patients with WD, other comparisons of various rating scales in WD have also been published. [125] As with other clinically applicable scores and indices, it is mandatory to review such calculations periodically, as experience with other prognostic instruments has shown that their reliability may need to be scrutinized [126] from time to time.…”
Section: Cu 1+mentioning
confidence: 99%